1997
DOI: 10.1099/00221287-143-7-2473
|View full text |Cite
|
Sign up to set email alerts
|

The properties and localization of Saprolegnia monoica chitin synthase differ from those of other fungi

Abstract: a n d Sa I om 6 n B a r t n i c k i -G a rc fa3 The presence of non-fibrillar a-chitin in cellulosic fungi (class Oomycetes) poses intriguing questions as to i t s role, subcellular localization and evolutionary significance. Previous studies reported on the similarity of chitin synthase from Saprolegnia monoica with that of other fungi. The present work describes important dissimilarities. There was no evidence that the chitin synthase of S. monoica was present in small low-density vesicles (chitosomes). Chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Previous studies on fungal chitin synthases also reported high molecular mass complexes of about 400-800 kDa when analyzed under non-denaturing conditions (Braun and Calderone, 1979;Hardy and Gooday, 1983;Kang et al, 1984;Leal-Morales et al, 1997;Machida and Saito, 1993;Montgomery et al, 1984;Ruiz-Herrera et al, 1980). However, these complexes were not explicitly assigned as chitin synthase oligomers.…”
Section: The Active Chitin Synthase Was Purified As An Oligomeric Commentioning
confidence: 84%
“…Previous studies on fungal chitin synthases also reported high molecular mass complexes of about 400-800 kDa when analyzed under non-denaturing conditions (Braun and Calderone, 1979;Hardy and Gooday, 1983;Kang et al, 1984;Leal-Morales et al, 1997;Machida and Saito, 1993;Montgomery et al, 1984;Ruiz-Herrera et al, 1980). However, these complexes were not explicitly assigned as chitin synthase oligomers.…”
Section: The Active Chitin Synthase Was Purified As An Oligomeric Commentioning
confidence: 84%
“…Even more intriguing is the presence of a fifth member of the GT family 2 that matches very strongly ( E value = 0) the putative chitin synthase gene from Magnaporthe grisea . Although no direct evidence exists favoring the presence of chitin in P. infestans cell wall, the existence of chitin synthase genes has been demonstrated in other oomycetes [54,55], suggesting that chitin is indeed produced in these species. We have cloned this gene from both P. infestans and P. sojae and preliminary experiments indicate that the gene is expressed in cultures grown in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Both organisms have a glucose-rich cell wall that in addition contains GlcNAc (12), and WGA labeling showed in both organisms that the GlcNAc components are not present only in the inner cell wall layers, in contrast to what is usually observed in true fungi (16,70,84). Leal-Morales et al (50) mentioned that the GlcNAc-containing material was uniformly distributed throughout the mycelial walls of Saprolegnia, a feature that is likely to occur also in Aphanomyces, as the proportion of GlcNAc in KOH-MeOH cell walls, where the amorphous superficial layers have been solubilized by treatment with hot KOH-MeOH, was the same as in crude cell walls. In Saprolegnia, however, the GlcNAc components are true crystalline chitin that accounts for only 0.7% of the cell wall and is not essential for hyphal growth (12), whereas in Aphanomyces these components are noncrystalline chitosaccharides that account for ca.…”
Section: Vol 7 2008 Aphanomyces Euteiches Cell Wall Chitosaccharidementioning
confidence: 99%
“…However, the cell wall of the closely related hyphochytridiomycetes contains both cellulose and chitin, and chitin was unambiguously detected by biophysical analyses in some oomycete species of the Leptomitale and Saprolegniale orders (2,12). In Saprolegnia monoica, a chitin synthase (CHS) activity was characterized in detail, and two CHS genes were identified, among which one was fully sequenced (50,54). In the Peronosporale and Pythiale orders, partial putative CHS sequences were identified in Plasmopara viticola and Phytophthora capsici (54,87).…”
mentioning
confidence: 99%